2020
DOI: 10.1002/jbm.b.34767
|View full text |Cite
|
Sign up to set email alerts
|

Radiological evaluations of low cost wollastonite nano‐ceramics graft doped with iron oxide in the treatment of induced defects in canine mandible

Abstract: Wollastonite with/without maghemite [(Fe2O3), 0, 3 and 10 wt%] was prepared by facile wet precipitation method. Effect of Fe2O3 presence in the obtained nano‐ceramics on physical structure, morphology, size and the mechanical features was evaluated using X‐ray diffraction, transmission electron microscope, and universal testing machine. Moreover, the in vitro biomineralization was examined using simulated body fluid (SBF) by means of scanning electron microscope/energy dispersive X‐ray, Fourier transform infra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 47 publications
0
9
0
Order By: Relevance
“…Pre-clinical experiments are needed to verify biocompatibility, biofunctionality, biodegradability, osteointegration, osteoinduction and osteoconduction characteristics of bone substitutes. The dog is an ideal model for evaluating bone repair and testing bone substitutes ( Taha et al, 2010 , Taha et al, 2018 , Mabrouk et al, 2021 , Mostafa et al, 2021 ). In terms of bone size and weight, trabecular bone density, and bone turn over, the dog's macro- and micro-structure is very comparable to human bone, making it an appropriate model in pre-clinical setting ( Abdel Hamid et al, 2020 , Abdel Hamid et al, 2021 , Mostafa et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Pre-clinical experiments are needed to verify biocompatibility, biofunctionality, biodegradability, osteointegration, osteoinduction and osteoconduction characteristics of bone substitutes. The dog is an ideal model for evaluating bone repair and testing bone substitutes ( Taha et al, 2010 , Taha et al, 2018 , Mabrouk et al, 2021 , Mostafa et al, 2021 ). In terms of bone size and weight, trabecular bone density, and bone turn over, the dog's macro- and micro-structure is very comparable to human bone, making it an appropriate model in pre-clinical setting ( Abdel Hamid et al, 2020 , Abdel Hamid et al, 2021 , Mostafa et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…It was concluded that CS-doped Fe 2 O 3 nanoparticle is biologically safe and biocompatible. Additionally, CBCT scanning did not reveal any periapical or peri -disc radiolucency denoting absence of inflammation, infection, or necrosis within the surrounding bone in association with promoted bone regeneration ( Mabrouk et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations